2021
DOI: 10.14202/vetworld.2021.964-971
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-related gene expression induced by Colombian propolis samples in canine osteosarcoma cell line

Abstract: Background and Aim: Osteosarcoma (OSA) is the most common bone tumor in canines and humans. This study aimed to assess the cytotoxic and apoptotic effects of Colombian propolis samples on a canine OSA cell line (OSCA-8) by evaluating the expression of BCL-2, BAX, CASPASE 9, CASPASE 8, and TNFR1 genes involved in the apoptosis pathway. Materials and Methods: After treating the cells with five Colombian propolis samples (Usm, Met, Fus, Sil, and Caj), we evaluated cell viability and lactate dehydrogenase (LDH) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[40] There is no information available on the ethnopharmacological activity of Colombian propolis associated with the antitumor effect, except for our own previous reports in which it was shown that EEP induced early and late apoptosis, related to the alteration of mitochondrial membrane potential, likewise, a significant decrease in the invasion, in canine osteosarcoma cells. [41,42] In the first place, the characterization consisted in evaluating proliferation, the exponential phase was established between 72 and 96 hr, a period of time in which the cell confluence was close to 70%, which could suggest that contact stimulates cell growth. These results coincide with tests carried out in the characterization of primary culture fibroblasts cultured with 10% SFB by other authors.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…[40] There is no information available on the ethnopharmacological activity of Colombian propolis associated with the antitumor effect, except for our own previous reports in which it was shown that EEP induced early and late apoptosis, related to the alteration of mitochondrial membrane potential, likewise, a significant decrease in the invasion, in canine osteosarcoma cells. [41,42] In the first place, the characterization consisted in evaluating proliferation, the exponential phase was established between 72 and 96 hr, a period of time in which the cell confluence was close to 70%, which could suggest that contact stimulates cell growth. These results coincide with tests carried out in the characterization of primary culture fibroblasts cultured with 10% SFB by other authors.…”
Section: Discussion Of Resultsmentioning
confidence: 99%